UPWELLING INFLUENCE ON ENVIRONMENTAL CHANGE AND SEDIMENTATION DYNAMICS FROM TRACE FOSSILS IN THE MOLUCCA SEA: IMPLICATIONS FOR SEDIMENT DATING - Wiguna, Taufan; Zuraida, Rina; Atmadipoera, Agus Saleh; Yuwono, Fareza Sasongko; Hernawan, Undang; Christanti, Vera; Tournier, Nicolas; Damanik, Adrianus; Vogel, Hendrik; Cahyarini, Sri Yudawati (Marine Geological Institute of Indonesia, 2025)
Bioturbation, the alteration of sediment layers by organism activities, plays a crucial role in shaping sedimentary environments. This process affects nutrient cycling, sediment stability, and habitat health, particularly in marine ecosystems like the Molucca Sea. Bioturbation can complicate age determination by disrupting the natural layering of sediments and potentially altering chronological records, which challenges the accuracy of dating methods. This study investigates bioturbation patterns and Zr/Rb ratios in sediment cores from the Molucca Sea to better understand past environmental conditions and assess the suitability of these sediments for age determination. Sediment samples were collected using a box corer from BUDEE22-29BC (within the upwelling region) and BUDEE22-57BC (outside the upwelling area). The cores were analyzed using CT scanning to identify bioturbation features, and the Bioturbation Index (BI) was applied to evaluate the intensity and impact of bioturbation on sediment dynamics. The Zr/Rb ratios were determined using an X-ray fluorescence (XRF) spectrometer, providing insights into grain size distribution. The results suggest the potential shifting of the upwelling center (BUDEE22-29BC) and variations in upwelling intensity (BUDEE22-57BC). Although Zr/Rb ratio shows that BUDEE22-29BC is a high-energy environment, as opposed to BUDEE22-57BC, both sites retain chronological integrity, making them suitable for paleoenvironmental and geochronological analysis.